Endosymbiotic bacteria in honey bees: Arsenophonus spp. are not transmitted transovarially - Yañez O. (2017)
© FEMS 2016. All rights reserved. Intracellular endosymbiotic bacteria are common and can play a crucial role for insect pathology. Therefore, such bacteria could be a potential key to our understanding of major losses of Western honey bees (Apis mellifera) colonies. However, the transmission and potential effects of endosymbiotic bacteria in A. mellifera and other Apis spp. are poorly understood. Here, we explore the prevalence and transmission of the genera Arsenophonus, Wolbachia, Spiroplasma and Rickettsia in Apis spp. Colonies of A. mellifera (N = 33, with 20 eggs from worker brood cells and 100 adult workers each) as well as mated honey bee queens of A. cerana, A. dorsata and A. florea (N = 12 each) were screened using PCR. While Wolbachia, Spiroplasma and Rickettsia were not detected, Arsenophonus spp. were found in 24.2% of A. mellifera colonies and respective queens as well as in queens of A. dorsata (8.3%) and A. florea (8.3%), but not in A. cerana. The absence of Arsenophonus spp. from reproductive organs of A. mellifera queens and surface-sterilized eggs does not support transovarial vertical transmission. Instead, horizontal transmission is most likely.